Present day causes of international friction and their elimination - American Association of Political & Social Science (Philadelphia American Academy of Political and Social Science, 1929)
War Debts,Reparations & The Liquidation of War Controls Difficulties involved in Reaching A Final Solution of The Reparations Problem